KONSEP ETIKA PERGAULAN PESERTA DIDIK DALAM SURAT AN-NUR AYAT 30-31 - Ariyaningsih, Shofia; Haryanto, Sri; Imam Agus Faisal, Vava (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The relevance of the concept of social ethics of students in QS. an-Nur verses 30-31 (towards life in the millennial era), life in the millennial era today is quite very sophisticated, where every information is easily accessed via the internet, they prefer mobile phones compared to TV, must have social media, do not like to read, know technology more than their parents. The lack of children is now competing to show their good popularity, which is the way of fashion style (clothing) various forms. Plus now there is an application that has been so very popular, and that is tik tok. Many elementary, junior high, high school, and adult children may join the trend. Whereas in Sura an-Nur itself verses 30-31 he commands men and women to bow their eyes and guard the genitals, not to show jewelry except what is usually shown, not to stomp feet when walking, and to wear khimar (hijab) for women